Hypothalamic hypernatremic myopathy: A single‐center case series. Issue 3 (9th January 2023) - Li, Qingjie; Bao, Lei; Liu, Meirong; Zhang, Ruixue; Shi, Hongjuan; Chen, Hao
Abstract: Introduction/Aims: Hypernatremia myopathy is a rare disease often unrecognized by clinicians. This study aimed to present a case series of hypernatremic myopathy with an emphasis on profiling its clinical characteristics and exploring its pathogenesis. Methods: We reviewed seven patients with hypernatremic myopathy and reported their demographic data, etiology, clinical manifestations, and laboratory and electrophysiological characteristics. A muscle biopsy was performed on one patient. Results: All patients had hypothalamic lesions as the cause of the hypernatremia including craniopharyngioma, germinoma, pituitary adenoma, Langerhans cell histiocytosis, and glioma. The clinical manifestations varied from mild weakness to complete paralysis. Myalgia and muscle cramps were also observed. Four of the patients had rhabdomyolysis on admission and developed acute kidney injury. All patients had markedly elevated serum creatine kinase (CK) and sodium levels. There was a significant positive correlation between serum sodium and CK levels. A high prevalence of hypopituitarism in different axes was observed in our study. Central hypogonadism (5 of 7), central hypothyroidism (3 of 7), and central diabetes insipidus (3 of 7) were the most common manifestations of hypothalamic dysfunction. Myopathic changes were observed on needle electromyography. The muscle biopsy of one patient showed diffuse necrotic fibers and scattered hypercontracted fibers with increased ragged red fibers. Discussion: Hypernatremia myopathy should be considered in hypernatremic patients with muscle weakness and myalgia. Rhabdomyolysis frequently occurs and may lead to acute kidney injury in hypernatremia myopathy. Testing of hormone levels and performance of brain magnetic resonance imaging for possible hypothalamic lesions is strongly recommended.